Gap analyses of information recorded in FishBase (and SeaLifeBase) for 12 countries - Bailly, Nicolas; Tilley, Alexander; Dam Lam, Rodolfo; Rossignoli, Cristiano (2024)
An evaluate the aquatic food data available for a given country through FishBase and SeaLifeBase databases. The choice of field analysed was made according to the T4R framework that has 5 components: taxon, territory, topic, time, reference.